Second-Degree Price Discrimination on Two-Sided Markets - Enrico Böhme (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
The paper provides an analysis of the second-degree price discrimination problem on a monopolistic two-sided market. In a simple framework with two distinct types of agents on market side 1, we show that under incomplete information the extent of platform access for high-demand agents is strictly reduced below the benchmark level with complete information. In addition, the paper finds that it is feasible in the monopoly optimum that the bundle for low-demand agents is more expensive than the one for high-demand agents if the extent of interaction with agents from the opposite market side is assumed to be bundle-specific.
Keywords: D42; D82; L12; 330